Measuring Sexual Motivation and Marital Satisfaction in Young Adult Men - Joya Redyana Trisnadevi Wahyu Rahmadyani; Annisa Ayu Lestari (Universitas Negeri Semarang, 2024)
Satisfaction is a crucial aspect of a marital relationship. The subjective nature of an individual's views and reactions to their marriage is a well-documented phenomenon. The potential for various risks to arise if individuals are dissatisfied with their marriage is considerable. One such risk is the potential for separation. One aspect of sexuality that can influence marital satisfaction is sexual motivation. One of the principal determinants of marital satisfaction is the individual's motive for engaging in sexual relations. The objective of this research is to ascertain the relationship between sexual motivation and marital satisfaction in young married adult men. This research employs quantitative methods. The subjects of this research were 604 participants. The sampling technique employed a purposive sampling approach, with the subjects comprising married young adult males, aged between 20 and 40 years. Marital satisfaction was gauged utilizing the Relationship Assessment Scale (RAS) instrument, while sexual motivation was quantified using the Multidimensional Sexual-Self Concept Questionnaire (MSCCQ) instrument. The results of Spearman's rho analysis indicate that the p value is .508, which is greater than .05. This indicates that there is no correlation between sexual motivation and marital satisfaction in young adult men. Further research is required to ascertain whether there are intervening variables that can explain the correlation between the two research variables